2022
DOI: 10.1002/1873-3468.14309
|View full text |Cite
|
Sign up to set email alerts
|

The TKFC Ala185Thr variant, reported as ‘null’ for fructose metabolism, is fully active as triokinase

Abstract: TKFC‐encoded triokinase catalyses glyceraldehyde phosphorylation in fructose metabolism and favours lipogenesis in mice. In Tkfc knockouts or knockdowns, fructose oxidation predominates over lipogenesis. The highly prevalent human variant Ala185Thr‐Triokinase/FMN cyclase (TKFC) has been reported to be ‘null’ for fructose metabolism, since Ala185‐TKFC rescues the mouse TKFC‐deficient phenotype, whereas Ala185Thr‐TKFC does not. Such report implies that most humans would display a noncanonical fructose metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In contrast, Thr185-TKFC is actually fully active as a triokinase/FMN cyclase, and a yeast growth assay revealed that Ala185-TKFC and Ala185Thr-TKFC overexpression rescued growth in Δdak1 yeast cells. These results suggest that human Thr185-TKFC cannot be considered a ‘null’ variant in terms of triokinase activity [ 86 ].…”
Section: Exogenous Fructose Metabolism and Chrebpmentioning
confidence: 99%
“…In contrast, Thr185-TKFC is actually fully active as a triokinase/FMN cyclase, and a yeast growth assay revealed that Ala185-TKFC and Ala185Thr-TKFC overexpression rescued growth in Δdak1 yeast cells. These results suggest that human Thr185-TKFC cannot be considered a ‘null’ variant in terms of triokinase activity [ 86 ].…”
Section: Exogenous Fructose Metabolism and Chrebpmentioning
confidence: 99%